2019
DOI: 10.3389/fnins.2019.01026
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid and Blood Cytokines as Biomarkers for Multiple Sclerosis: A Systematic Review and Meta-Analysis of 226 Studies With 13,526 Multiple Sclerosis Patients

Abstract: Background: Multiple sclerosis (MS) biomarker identification is important for pathogenesis research and diagnosis in routine clinical practice. Cerebrospinal fluid (CSF) and blood cytokines as potential biomarkers that can inform MS pathogenesis, diagnosis and response to treatment have been assessed in numerous studies. However, there have been no comprehensive meta-analyses to pool cytokine data and to address their diagnostic performance. We systematically reviewed literature with meta-analyses to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…To definitively establish the role of IL-15 in EAE and to mimic the elevated IL-15 levels we and others detected in the blood of patients with MS, 2 , 22 we investigated the impact of increasing peripheral levels of IL-15 after disease onset. We used the same approach as published by others and injected the biologically active form of IL-15 precomplexed with IL-15Rα.…”
Section: Resultsmentioning
confidence: 99%
“…To definitively establish the role of IL-15 in EAE and to mimic the elevated IL-15 levels we and others detected in the blood of patients with MS, 2 , 22 we investigated the impact of increasing peripheral levels of IL-15 after disease onset. We used the same approach as published by others and injected the biologically active form of IL-15 precomplexed with IL-15Rα.…”
Section: Resultsmentioning
confidence: 99%
“…We chose the random-effects model for the study if there was significant between-study heterogeneity 10 , and the rest were performed by a fixed-effect model. Furthermore, sensitivity analysis 27 , I 2 statistic and Cochrane Q test 28 , metaregressions 29 , and Egger's test 30 were performed as previously described. Statistical significance was set at P < 0.05 in the present meta-analysis, an exception was the Cochrane Q test (P < 0.10 was considered statistically significant).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Sclerosis (MS) is a chronic autoimmune and neuro-inflammatory disease of the central nervous system characterized by damage to myelinated axons with varying degrees of destruction of myelin and axons [ 73 , 74 ]. In a meta-analysis, which reviewed 226 research papers and 13,526 patients, Bai et al (2019) found that 13 CSF cytokines (from a list of 26) and 21 blood cytokines (from a list of 37) were elevated in MS as compared with controls and that CSF CCL-11 was significantly increased with a large effect size in patients with MS [ 75 ]. Huber et al (2018) reported that during the relapse phase, CCL-11 may be downregulated, while during the secondary progressive phase, CCL-11 is upregulated to achieve plateau levels [ 40 ].…”
Section: Resultsmentioning
confidence: 99%